GPR40 Agonism Modulates Inflammatory Reactions in Vascular Endothelial Cells - Joo Won Kim; Eun Roh; Kyung Mook Choi; Hye Jin Yoo; Hwan-Jin Hwang; Sei Hyun Baik (Diabetes & Metabolism Journal, 2022)
Endothelial dysfunction is strongly linked with inflammatory responses, which can impact cardiovascular disease. Recently, G protein-coupled receptor 40 (GPR40) has been investigated as a modulator of metabolic stress; however, the function of GPR40 in vascular endothelial cells has not been reported. We analyzed whether treatment of GPR40-specific agonists modulated the inflammatory responses in human umbilical vein endothelial cells (HUVECs). Treatment with LY2922470, a GPR40 agonist, significantly reduced lipopolysaccharide (LPS)-mediated nuclear factor-kappa B (NF-κB) phosphorylation and movement into the nucleus from the cytosol. However, treatment with another GPR40 agonist, TAK875, did not inhibit LPS-induced NF-κB activation. LPS treatment induced expression of adhesion molecules vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) and attachment of THP-1 cells to HUVECs, which were all decreased by LY2922470 but not TAK875. Our results showed that ligand-dependent agonism of GPR40 is a promising therapeutic target for overcoming inflammatory reactions in the endothelium.